SKALA KESANTUNAN TUTURAN IMPERATIF PADA DRAMA GOKUSEN 1 (EPISODE 1-5) - Nani Anggraini; Zuli Laili Isnaini; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This study discusses the politeness scale imperative speech in drama Gokusen 1 episode 1-5. The purpose of this study was to knowing the politeness scale used in imperative speech and determine the factors that influence politeness. The object of research is figures in the drama Gokusen 1 episode 1-5. This study is qualitative descriptive by interpreting the object under study based on the theory of politeness by Leech (1983). Data obtained by listening to imperative speech which used figures and noted then group them into each type of imperative. From the result of research, indicates that the characters in the drama Gokusen using five types of politeness scale by Leech. Cost-benefit scale used in data “Hikkomeya! (go out!)”. Optionality scale used in data “eiga wo mi ni ikimasenka? (will go to the cinema?)”. Indirectness scale used in data “kiite! (listen!)”. Authority scale used in data “yamero! (stop it!)”, and social distance scale used in data “Ganbare! (fighting!)”. In this study are also often found students who used the speech is not polite to the teacher. It is uncommon in everyday life. In addition, there are some factors that influence the politeness of the each speech.Key Word: Politeness Scale, Imperative Speech